Comparative Studies on Growth Performance of Probiotic Supplemented Rohu Labeo rohita Fingerlings - Gohila, B (International Journal of Pharmaceutical & Biological Archive, 2013)
Comparative Studies on Growth Performance of Probiotic Supplemented Rohu Labeo rohita Fingerlings